The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1186/1475-2875-10-327
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring fever treatment behaviour and equitable access to effective medicines in the context of initiatives to improve ACT access: baseline results and implications for programming in six African countries

Abstract: BackgroundAccess to artemisinin-based combination therapy (ACT) remains limited in high malaria-burden countries, and there are concerns that the poorest people are particularly disadvantaged. This paper presents new evidence on household treatment-seeking behaviour in six African countries. These data provide a baseline for monitoring interventions to increase ACT coverage, such as the Affordable Medicines Facility for malaria (AMFm).MethodsNationally representative household surveys were conducted in Benin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
143
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(165 citation statements)
references
References 28 publications
12
143
6
Order By: Relevance
“…The sale mirrors the stock of AMDs found on drug audit, which showed that CQ and SP still had dominion of the market. These findings are in consonance with other studies in Nigeria 21,26,27 and elsewhere 19,22 where, despite change in treatment policy, formerly used AMDs were still on sale in drug shops even years after the change. The wide availability and sale of CQ and SP implies that many cases of uncomplicated malaria were still receiving inappropriate treatment with consequences including progression to severe illness, increased mortality and growing drug resistance.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The sale mirrors the stock of AMDs found on drug audit, which showed that CQ and SP still had dominion of the market. These findings are in consonance with other studies in Nigeria 21,26,27 and elsewhere 19,22 where, despite change in treatment policy, formerly used AMDs were still on sale in drug shops even years after the change. The wide availability and sale of CQ and SP implies that many cases of uncomplicated malaria were still receiving inappropriate treatment with consequences including progression to severe illness, increased mortality and growing drug resistance.…”
Section: Discussionsupporting
confidence: 81%
“…18 Studies have shown that despite change in antimalarial drug policy, both providers and consumers continued to use the erstwhile drugs for a long time for various reasons. [19][20][21][22] This slow adoption is not without consequences as the problems that necessitated the change remain.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Uganda also show that only about a quarter of pregnant women receive two doses of IPTp with SP. 48 However, these findings are in contrast with studies conducted in Central Mozambique 59 Most children under 5 years of age and pregnant women in Nigeria often have a poor economy that constraint them from seeking the best medical care. This group constitute a larger percentage of the Nigerian population and are prone to infectious diseases.…”
Section: Discussioncontrasting
confidence: 55%
“…34 As is common in the rest of Uganda, Luwero residents frequently treat episodes of suspected malaria with over-the-counter medicines at formal or informal retail shops and pharmacies. 22,35 At the time, approximately 44% of drug shops in Uganda sold ACTs, though these drugs were expensive, costing roughly five times as much as the most popular antimalarial drug, sulfadoxinepyrimethamine. 23 Consequently, at the time of study launch, only about 23% of suspected malaria episodes among children under the age of 5 years were being treated with ACTs in Uganda.…”
Section: Methodsmentioning
confidence: 99%
“…[17][18][19][20] We hypothesized that an important driver of nonadherence is diagnostic uncertainty, as few patients with suspected malaria receive diagnostic confirmation of malaria via blood test. 1,21,22 At the time of the study, malaria diagnostic testing was available in 35% of public health facilities in Uganda (4% had rapid diagnostic tests [RDTs]), 47% of private facilities, and 4% of private drug shops. 23 Since the symptoms of malaria overlap with several common diseases such as pneumonia, as well as other bacterial and viral infections, [24][25][26] untested patients may face significant uncertainty over whether the illness they are suffering from is malaria, particularly in contexts where they have less confidence in the provider's ability to clinically diagnose the disease.…”
Section: Introductionmentioning
confidence: 99%